2011
DOI: 10.1016/j.cub.2011.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling of Activation and Effector Binding Underlies ARF6 Priming of Fast Endocytic Recycling

Abstract: The small GTP-binding protein ADP-ribosylation factor 6 (ARF6) controls the endocytic recycling pathway of several plasma membrane receptors. We analyzed the localization and GDP/GTP cycle of GFP-tagged ARF6 by total internal reflection fluorescent microscopy. We found that ARF6-GFP associates with clathrin-coated pits (CCPs) at the plasma membrane in a GTP-dependent manner in a mechanism requiring the adaptor protein complex AP-2. In CCP, GTP-ARF6 mediates the recruitment of the ARF-binding domain of downstre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
55
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 33 publications
12
55
1
Order By: Relevance
“…Arf5-GFP was more diffusely distributed on the plasma membrane but could also be observed in puncta that colocalized with clathrin. In agreement with a recent report (24), Arf6-GFP also displayed colocalization with clathrin-positive structures (Fig. 6, G-I).…”
Section: Brag2 Interacts With Clathrin Heavy Chain and Ap-2-tosupporting
confidence: 81%
See 1 more Smart Citation
“…Arf5-GFP was more diffusely distributed on the plasma membrane but could also be observed in puncta that colocalized with clathrin. In agreement with a recent report (24), Arf6-GFP also displayed colocalization with clathrin-positive structures (Fig. 6, G-I).…”
Section: Brag2 Interacts With Clathrin Heavy Chain and Ap-2-tosupporting
confidence: 81%
“…Montagnac et al (24) recently reported that Arf6 concentrates in clathrin-coated pits but that it is not necessary for endocytosis of transferrin receptors. Using a fluorescently tagged fragment of the Arf6 effector protein, JIP3, these authors demonstrated that Arf6 is active in clathrin-coated vesicles, but is not accessible to JIP3 until a later time when the vesicles uncoat (24).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a separation of Arf6 activation and effector functions has been observed in endocytic receptor recycling, in which a dormant pool of Arf6-GTP was observed in clathrin-coated pits that became mobilized only later in fast endocytic events (44). This finding would be consistent with the proposed role of EFA6 in sustaining a basal amount of Arf6-GTP.…”
Section: Discussionsupporting
confidence: 79%
“…A model for Arf6 acting at sites quite distant from its site of activation has recently been proposed (67), but the actions of Arf6 at the cell surface differ substantially from those of Arfs 1-5 on endomembranes so it is not clear how comparable these studies will prove to be. We currently lack direct evidence of specific cargo-GEF-Arf complex formation and must also consider additional components acting between the cargo and the Arf GEFs.…”
Section: Gga1mentioning
confidence: 99%